2021
DOI: 10.3389/fonc.2021.610303
|View full text |Cite
|
Sign up to set email alerts
|

The Crosstalk Between Tumor Cells and the Immune Microenvironment in Breast Cancer: Implications for Immunotherapy

Abstract: Breast cancer progression is a complex process controlled by genetic and epigenetic factors that coordinate the crosstalk between tumor cells and the components of tumor microenvironment (TME). Among those, the immune cells play a dual role during cancer onset and progression, as they can protect from tumor progression by killing immunogenic neoplastic cells, but in the meanwhile can also shape tumor immunogenicity, contributing to tumor escape. The complex interplay between cancer and the immune TME influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
122
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(137 citation statements)
references
References 206 publications
(271 reference statements)
1
122
0
2
Order By: Relevance
“…Therefore, clusters of these heterotypic components of TME could be revealed by MALDI-MSI. The immune system plays an important role in cancer progression, either by eliminating cancer cells or by stimulating tumor growth [60,61]. It is noteworthy that tumor infiltration by lymphocytes indicated an antitumor response of breast cancer, and the level of tumor-infiltrating lymphocytes (TILs) was associated with a better outcome in HER2-positive cancers [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, clusters of these heterotypic components of TME could be revealed by MALDI-MSI. The immune system plays an important role in cancer progression, either by eliminating cancer cells or by stimulating tumor growth [60,61]. It is noteworthy that tumor infiltration by lymphocytes indicated an antitumor response of breast cancer, and the level of tumor-infiltrating lymphocytes (TILs) was associated with a better outcome in HER2-positive cancers [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…IDO expression was correlated with increased tumor-infiltrating T regulatory cells (T reg); studies had suggested that tumor cells or IDO-expressing APCs could mediate T reg cells to strongly dampen the antitumor responses of T cells ( 16 , 39 ). The intratumor ratio of infiltrating lymphocytes (TILs) to T reg cells was considered as a marker of favorable immunological responses, which was a possible key factor to control tumor progression ( 5 , 55 ). Previous work showed that intratumoral γδ T cell numbers were positively correlated with advanced tumor stages, HER2 expression status, FOXP3 + cells, and high lymph node metastasis, but inversely correlated with relapse-free survival and overall survival of breast cancer patients ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is controlled by EBV-miR-BART7 and EBV-miR-BART2-5p [135,295] negatively interfering with NK cell responses. The enhanced recruitment and activation of Tregs, the subsequent anergy of CD8 + cytotoxic T cells, the crosstalk with tumor-growth-promoting M2 macrophages and the overexpression of the immune-suppressive enzyme indoleamine 2,3-deoxygenase (IDO) are also involved in immune evasion [296][297][298]. Innate immune cells play an important role in the host response against viral infections including EBV [294].…”
Section: Altered Regulation Of Inflammatory Signal Transduction Pathways and Soluble Factorsmentioning
confidence: 99%